An introduction to qualitative research - Flick, Uwe 1956- (SAGE, 2018)
The definitive guide to the full qualitative research process, from design to dissemination, this is everything you need to understand how good quality research is produced, and how to use and enrich your own work with it. New to this edition: - A new structure follows the research process step-by-step - Brand new chapter on digital methods and social media data explores cutting-edge research - Multi-disciplinary case studies give you real research examples whatever your subject - Focused reading exercises help you explore the literature and build a better bibliography - Integrated online resources, to master the key concepts, discover real research and track your progress An Introduction to Qualitative Research has everything a social science student needs to understand and explore the richness of qualitative research.